(untitled) (BALEAP Journal of Research and Practice, 2025)
The Summer Pre-sessional (SPS) can be a difficult place to operate. Intensive working environments; tight turnarounds; unpaid overtime - these realities are revealed in the casual language of recovery that the EAP community instinctively reaches for when describing our signature summer programmes and which provided the initial inspiration for a talk at the 2023 BALEAP Conference: a critical reflection on the SPS. This paper offers an extended and ongoing reflection, incorporating the essential content of that original paper as well as the wider conference tone where uncertainty over the longer-term health of the SPS was evident. It is hoped that, with reflective distance and modest adjustments, some sense of a more hopeful future for the Pre-sessional may emerge, one that recentres community and exercises some quiet resistance to prevailing metrics of success.